Rational selection of building blocks for the assembly of bispecific antibodies. Issue 1 (1st January 2021) - Gong, Danyang; Riley, Timothy P.; Bzymek, Krzysztof P.; Correia, Ana R.; Li, Danqing; Spahr, Christopher; Robinson, John H.; Case, Ryan B.; Wang, Zhulun; Garces, Fernando
ABSTRACT: Bispecific antibodies, engineered to recognize two targets simultaneously, demonstrate exceptional clinical potential for the therapeutic intervention of complex diseases. However, these molecules are often composed of multiple polypeptide chains of differing sequences. To meet industrial scale productivity, enforcing the correct quaternary assembly of these chains is critical. Here, we describe Chain Selectivity Assessment (CSA), a high-throughput method to rationally select parental monoclonal antibodies (mAbs) to make bispecific antibodies requiring correct heavy/light chain pairing. By deploying CSA, we have successfully identified mAbs that exhibit a native preference toward cognate chain pairing that enables the production of hetero-IgGs without additional engineering. Furthermore, CSA also identified rare light chains (LCs) that permit positive binding of the non-cognate arm in the common LC hetero-IgGs, also without engineering. This rational selection of parental mAbs with favorable developability characteristics is critical to the successful development of bispecific molecules with optimal manufacturability properties.